Poésie et politique dans les mondes normands médiévaux (IXe-XIIIe siècle) Poetry and Politics in the Viking and Norman Diasporas (Ninth-Thirteenth Centuries) (Calenda, 2020)
Le colloque interrogera les rapports entre poésie et pouvoir en favorisant les échanges entre historiens et spécialistes des littératures latines et vernaculaires des mondes normands médiévaux aux IXe-XIIIe siècle. On étudiera les poèmes composés sur un vaste territoire – celui des diasporas vikings et normandes, de l’Islande à l’Italie méridionale (îles Britanniques, Scandinavie, Rus’ kiévienne, une partie de l’Orient latin) – pour examiner la manière dont la poésie (1) s’inscrit dans un contexte politique particulier (poésie encomiastique, satirique) (2) est le lieu d’une représentation des pouvoirs politiques ou de transmission de conceptions morales ou religieuses (miroirs des princes, poésie didactique, gnomique) (3) peut être préférée à la prose pour véhiculer des idées politiques. The conference will address the relationships between poetry and power in the medieval world, fostering exchanges between historians and scholars in the fields of Latin and vernacular literatures. The poems under scrutiny will be those composed in the Viking and Norman diasporas between the ninth and the thirteenth century, covering a wide geographical expanse, from Iceland to Southern Italy, through Britain and Ireland, Scandinavia, Kievan Rus’ and part of the Latin East. The main questions which will be studied are: (1) the specific context for the composition of political poetry (e.g. encomiastic or satiric); (2) poetry as a means for the representation of power or the transmission of moral or religious conceptions (e.g. mirrors for princes, didactic or gnomic poetry); (3) the reasons for preferring poetry over prose in order to convey political ideas.